Doping and Anisotropy–Dependent Electronic Transport in Chalcogenide Perovskite CaZrSe3 for High Thermoelectric Efficiency. Issue 9 (3rd July 2019) - Osei‐Agyemang, Eric; Enninful Adu, Challen; Balasubramanian, Ganesh
Abstract: The potential of an environmentally friendly and emerging chalcogenide perovskite CaZrSe3 for thermoelectric applications is examined. The orthorhombic phase of CaZrSe3 has an optimum band gap (1.35–1.40 eV) for single‐junction photovoltaic applications. The predictions reveal that CaZrSe3 possesses an absorption coefficient of ≈4 × 10 5 cm −1 at photon energies of 2.5 eV with an early onset of optical absorption (≈0.2 eV) well below the optimum band gap. Seebeck coefficient, S, is inversely proportional to the carrier mobility as the calculated average effective mass for electrons is higher than for holes; p ‐type doping enhances the electrical conductivity, σ. The electronic thermal conductivity κe remains low at all temperatures. The upper limit of the thermoelectric figure of merit (ZT e ) attains ≈1.0 when doped at specific chemical potentials, while a high Seebeck coefficient contributes to the ZT e  = 1.95 at 50 K for p ‐type doping with 10 18 cm −3 carrier concentration, demonstrating high thermoelectric efficiency. Abstract : First principles calculations employed to predict the thermoelectric properties of CaZrSe3 prove that the chalcogenide perovskite possesses good thermoelectric efficiency through a combination of high Seebeck coefficient and low electronic thermal conductivity, while significant anisotropy is noted in the material properties.